ANALISIS ALIH FUNGSI LAHAN DAN PENGARUHNYA TERHADAP EKOSISTEM PESISIR PANTAI SANTOLO DI KABUPATEN GARUT - zabatuddawat, Isti (Universitas Nusa Cendana, 2025)
This study aims to analyze changes in land use and its impact on the coastal ecosystem in the Santolo Beach area, Garut Regency. The method used is descriptive qualitative with indirect observation through searching various digital sources, such as photos, videos, tourist reports, news articles, and data from related agencies to see the interaction between coastal ecological aspects and tourism development activities. The results of the study indicate that land use changes in Santolo Beach have triggered abrasion and accretion due to the reduction of coastal vegetation as a natural protector, accompanied by increased pollution from plastic waste and domestic waste that threaten marine biota such as small fish, mollusks, and coral reefs. This condition has an impact on decreasing fishermen's catches, increasing the vulnerability of tourism infrastructure to abrasion, and causing ecological and socio-economic pressures. The main factors causing land use changes include economic drivers, social changes in society, and weak spatial planning regulations. Therefore, an ecotourism-based management strategy and community involvement in conservation are needed to maintain a balance between tourism development and the sustainability of the Santolo Beach coastal ecosystem.